ChemInform Abstract: Synthesis of BF3 Catalyzed Mannich Derivatives with Excellent ee from Phenylpropanolamine, Study of Their Antimicrobial Activity and Molecular Docking. Issue 5 (January 2016) - Chennakesava Rao, K.; Easwaramoorthi, K.; Arun, Y.; Balachandran, C.; Muralidhara Rao, K. S.; Govindhan, M.; Emi, Nobuhiko; Prakasam, T.; Perumal, P. T.
Abstract: Antimicrobial agents [(IV) and (VI)] are synthesized with 100% e.e.